READING ANXIETY, READING SELF-EFFICACY AND VOCABULARY AS PREDICTORS OF STUDENTS’ READING COMPREHENSION - Has riati (Yayasan Akrab Pekanbaru, 2019)
The present study endeavored to examine whether reading anxiety, reading self-efficacy and vocabulary contribute towards students’ reading comprehension and which one of these factors that serves as the better predictor of students’ reading comprehension among 82 the second semester students of English department at Halu Oleo University. Questionnaires are employed for measuring students’ reading anxiety and reading self-efficacy, vocabulary test for measuring students’ vocabulary. Whereas, reading comprehension test for measuring students’ reading comprehension. The result revealed reading anxiety contributes towards students’ reading comprehension, reading self-efficacy contributes towards students’ reading comprehension and vocabulary contributes towards students’ reading comprehension. Vocabulary is higher than reading anxiety and reading self-efficacy in predicting students’ reading comprehension when these factors are examined simultaneously. Importantly, this study leads to the conclusion that vocabulary is better and stronger predictor of students’ reading comprehension than students’ reading anxiety and students’ reading self-efficacy. Taking importance of vocabulary into consideration, therefore language teachers should put more emphasize on students’ vocabulary, particularly endeavor to make their vocabulary knowledge wider and deeper.